PENGARUH STRES KERJA DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA (Studi Pada Perawat RS. Amelia Pare) - Ilhami, Susanti Dwi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims at analyzing the influence of job stress and organizational climate on the job satisfaction of nurses in Amelia Pare Hospital. The sample frame of this study is all regular nurses in Amelia Pare Hospital, i.e. 64 people. The research uses census sampling technique. A number of 62 questionnaires was completed and used as primary data. The method used to collect the data from respondents is questionnaires using Likert scale. The data are analyzed through multiple linear regression analysis using SPSS version 16. The independent variables in this study are job stress (X1) and organizational climate (X2), while the dependent variable is job satisfaction (Y). The results of this study show that job stress (X1) and organizational climate (X2) simultaneously and partially significant in influencing job satisfaction (Y). In addition, organizational climate (X2) gives a dominant influence on the dependent variables.Keywords: job stress, organizational climate, job satisfaction